Key Microbes and Metabolic Potentials Contributing to Cyanide Biodegradation in Stirred-Tank Bioreactors Treating Gold Mining Effluent. (3rd March 2020) - Shin, Doyun; Park, Jeonghyun; Park, Hyunsik; Lee, Jae-Chun; Kim, Min-Seuk; Lee, Jaeheon
ABSTRACT: Microbial community and metabolic potential changes in a biological wastewater treatment reactor were investigated using phylogenetic and functional profile analysis from 16S rRNA-gene-based pyrosequencing. Stirred-tank bioreactors fed by cyanide-containing synthetic solutions were inoculated with a sewage sludge and the cyanide-degrading microbial consortium. A better cyanide degradation was observed in the reactors containing the phylum Proteobacteria, but lower efficiency was observed when Firmicutes and Bacteroidetes were dominant. This study shows the important role of phylum Proteobacteria for the cyanide-containing wastewater treatment in the gold processing plant and contributes the fundamentals about the microbial community exposed to the cyanide.